Hukum Riba dan Relevansinya terhadap Bunga Bank Perspektif Hukum Ekonomi Islam - Hardiati, Neni; Ibrahim, Ahmad Zaki; F, Fitriani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Riba is a transaction that is prohibited in Islamic economic activities. This study aims to look at the views of the previous to contemporary scholars regarding usury and gharar. The method used is a literature study, which is carried out by collecting, studying and reviewing books, scientific magazines and related documents such as theses and scientific journals. is still a debate among classical and contemporary scholars. Classical scholars still adhere to the Qur'anic texts that usury is haram, but contemporary scholars such as Fazlur Rahman view usury on bank interest as permissible as long as it does not harm others for moral reasons, but the Indonesian Ulema Council mentions in its fatwa that bank interest includes usury. jahiliyah. Then the MUI stated that bank interest included usury. KHES prohibits activities that contain elements of usury and gharar